Heavy metal distribution and soil-plant transfer around a municipal landfill: Evidence from Clarke concentration and biological uptake coefficients - Atoyeva, Gulhayo; Jabbarov, Zafarjon; Sayitov, Sardor; Aliboyeva, Malika; Atabekova, Dilaram; Ruzmetov, Rasul; Xalikova, Liliya; Rakhmatullaeva, Guljakhon; Karabekov, Otabek; Reymova, Feruza; Abdullaev, Shokhrukh (Brawijaya University, 2026)
Municipal solid waste landfills are important sources of heavy metal contamination in surrounding ecosystems. This study evaluates the spatial distribution and soil–plant transfer of heavy metals around the Ohangaron municipal landfill in the Tashkent region, Uzbekistan. Soil and plant samples were collected at distances of 1.0 and 2.5 km from the landfill in four cardinal directions. Concentrations of Fe, Co, Ni, and Mo were determined using inductively coupled plasma optical emission spectrometry (ICP-OES). Soil contamination levels were assessed using Clarke concentration coefficients and technogenic enrichment factors, while plant uptake was evaluated through biological uptake coefficients (BUC). The results showed heterogeneous spatial distribution of heavy metals. Iron concentrations remained within natural background levels, whereas molybdenum exhibited strong technogenic enrichment, exceeding Clarke values by up to 10-30 times in several locations. Nickel and cobalt displayed moderate contamination patterns associated with landfill influence. Bioaccumulation analysis indicated moderate uptake of Fe, Co, and Ni by plants, while molybdenum demonstrated higher mobility and accumulation capacity. The findings highlight the environmental impact of landfill activities and emphasize the need for continuous monitoring and improved waste management practices.